Aminophylline-associated irritable behaviour in preterm neonates. (August 2016) - Maeda, Tomoki; Inoue, Masanori; Sekiguchi, Kazuhito; Ihara, Kenji
Abstract: Aim: This study investigated the effect of aminophylline on behaviour and autonomic function in the preterm period. Method: Subjects were preterm infants cared for in the Oita University hospital from August 2012 to October 2014. The group that was administered aminophylline (Am +) and the group that received no aminophylline (Am −) included 11 cases that exhibited a mean gestational age of 28 weeks 5 days and a mean birth weight of 1109 g and 8 cases that exhibited a mean gestational age of 30 weeks 5 days and a mean birth weight of 1223 g, respectively. Intravenous aminophylline was administered continuously at a dose of 4–6 mg/kg/day followed by oral therapy when the infant suffered repetitive apnoea. Two-hour video recordings were obtained every 2 weeks, and electrocardiograms were performed simultaneously. Onset-offset and tremulous movements in general movement (GM) optimality list were used as indices of behaviour. Autonomic functions were investigated via heart-rate and heart-rate variability measurements using frequency domain spectral analysis and the MemCalc method. We compared indices in 4 periods: 30–31, 32–33, 34–35 and 36–37 weeks gestation. Results: The Am + group exhibited significantly low optimality of tremulous movements at 32–33 weeks gestation. The autonomic parameters did not differ significantly between the Am + and Am − groups. There was no significant correlation between GMs optimality score and serum theophylline concentration. Conclusion: Aminophylline administration was associated with transient irritable behaviour without autonomic changes in the preterm period.